2022
DOI: 10.3390/antiox11091678
|View full text |Cite
|
Sign up to set email alerts
|

The Azadirachta indica (Neem) Seed Oil Reduced Chronic Redox-Homeostasis Imbalance in a Mice Experimental Model on Ochratoxine A-Induced Hepatotoxicity

Abstract: Liver damage severity depends on both the dose and the exposure duration. Oxidative stress may increase the Ochratoxine-A (OTA) hepatotoxicity and many antioxidants may counteract toxic liver function. The present study aims to investigate the hepatoprotective potential of Azadirachta indica A (A.indica; neem oil) seed oil to reduce acute oxidative disorders and residual OTA toxicity in a 28-day experimental model. The activity of antioxidant and hepatic enzymes, cytokines and the levels of oxidative stress bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Antioxidant activities of neem leaves from India (Wandscheer et al, 2004), England (Salehzadeh et al, 2003), Nepal (Ghimeray et al, 2009, Brasil (Nagano and Batalini 2021), Thailand (Sithisarn et al, 2006), Nigeria (Olaitan et al, 2021 have also been reported. Neem leaves and oil were reported maximum antioxidant activity % because of its phenolic compounds and enormous scavenger ability towards free radical (Nikolova et al, 2022;Nakamura et al, 2022). These observations are a close agreement to the current study.…”
Section: Fig2 H 2 O 2 Scavenging Activity (%) Of Azadirachta Indicasupporting
confidence: 93%
“…Antioxidant activities of neem leaves from India (Wandscheer et al, 2004), England (Salehzadeh et al, 2003), Nepal (Ghimeray et al, 2009, Brasil (Nagano and Batalini 2021), Thailand (Sithisarn et al, 2006), Nigeria (Olaitan et al, 2021 have also been reported. Neem leaves and oil were reported maximum antioxidant activity % because of its phenolic compounds and enormous scavenger ability towards free radical (Nikolova et al, 2022;Nakamura et al, 2022). These observations are a close agreement to the current study.…”
Section: Fig2 H 2 O 2 Scavenging Activity (%) Of Azadirachta Indicasupporting
confidence: 93%
“…Oxidative stress is caused by an imbalance between ROS production and antioxidant capacity (Tang et al, 2019). Cells have a variety of mechanisms to prevent damage caused by oxidative stress, including enzyme systems (such as SOD, CAT, and GSH‐Px) and endogenous antioxidant molecules (such as GSH), which are also important parameters for measuring oxidative damage (Nikolova et al, 2022). We found that IBC induced the increase of ROS and MDA and the decrease of CAT, GSH and GSH‐Px in Zebrafish embryos and HepG2 cells, indicating that IBC induced oxidative stress damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nimbolide showed to regulate the ROS redox-homeostatic imbalance and the immune modulatory response after Ochratoxin A (OTA)-induced acute liver inflammation in mouse models. The anti-inflammatory effect of nimbolide was found to be mediated by inhibiting cytokine production and decreased oxidative stress, via regulating protein peroxidation, protein expression of SIRT1-mediated pathways and protein carbonyl content (PC) ( 73 ). In addition, nimbolide can prevent cisplatin-induced hepatotoxicity and nephrotoxicity ( 74 ).…”
Section: Protective Effects Of Nimbolide With Different Mechanisms In...mentioning
confidence: 99%